Nitrogen removal and microbial mechanisms in a novel tubular bioreactor‐enhanced floating treatment wetland for the treatment of high nitrate river water. (8th August 2022) - Cui, He; Yang, Yinchuan; Zhang, Xin; Dong, Lei; Yang, Yifeng; Huang, Minsheng; He, Yan; Lu, Xueqin; Zhen, Guangyin
Abstract: A novel tubular bioreactor‐enhanced floating treatment wetland (TB‐EFTW) was developed for the in situ treatment of high nitrate river water. When compared with the enhanced floating treatment wetland (EFTW), the TB‐EFTW system achieved 30% higher total nitrogen removal efficiency. Further, the average TN level of the TB‐EFTW effluent was below the Grade IV requirement (1.5 mg/L) specified in Chinese standard (GB3838‐2002). Microbial analysis revealed that both aerobic and anoxic denitrifying bacteria coexisted in the new system. The relative abundance of aerobic and anoxic denitrifiers were 42.69% and 22% at the middle and end of the tubular bioreactor (TB), respectively. It is reasonable to assume that effective nitrogen removal can mainly be attributed to the addition of solid carbon source and the spatial difference in DO distribution (oxic–anoxic areas in sequence) inside the TB. The initial investment cost and operating costs associated with the TB‐EFTW system are approximately 14, 000 and 3500 yuan per 1000 m 3 river water, respectively. Considering its low cost, minimal maintenance requirements, and effective nitrogen removal, this newly developed system can be regarded as a promising technology for treating high nitrate river water. Practitioner Points: A novel TB‐EFTW system was developed to upgrade traditional in situ treatment techniques. The TB‐EFTW could achieve 30% higher nitrogen removal efficiency than EFTWs. Both aerobic and anoxic denitrifying bacteria coexisted in the system. The system shows better technical and economic performance compared with routine techniques. Abstract : A novel, simple, cost‐effective, and high total nitrogen removal tubular bioreactor‐enhanced floating treatment wetland (TB‐EFTW) was developed, which achieved high total nitrogen removal from polluted river water.